Brain functional connectivity changes on fMRI in patients with chronic pelvic pain treated with the Neuro Emotional Technique: a randomised controlled trial - Daniel A. Monti; Faezeh Vedaei; Anna Tobia; Emily Navarreto; Chloe Hriso; Reneita Ross; Rohit Raja; Nancy Wintering; George P. Zabrecky; Feroze Mohamed; Andrew B. Newberg (Journal of Obstetrics and Gynaecology)
Background Chronic pelvic pain is a substantial clinical challenge that profoundly impacts quality of life for many women. The Neuro Emotional Technique (NET) is a novel mind-body intervention designed to attenuate emotional arousal of distressing thoughts and pain. This study evaluated functional connectivity changes in key areas of the brain in patients with chronic pelvic pain receiving the NET intervention. The goal was to assess whether the NET intervention was associated with functional connectivity (FC) changes in the brain related to reductions in emotional distress and pain, particularly in the limbic areas, sensory/pain regions, and cerebellum.Methods This is a prospectively designed study that included twenty-six patients with a diagnosis of chronic pelvic pain who were randomised to either the NET intervention or a waitlist control. To evaluate the primary outcome of neurophysiological effects, all participants received resting state functional blood oxygen level dependent (BOLD) magnetic resonance imaging (rs-fMRI) before and after the NET intervention or waitlist control period. Pain, mood, anxiety, and quality of life also were assessed.Results Compared to the control group, the NET group demonstrated significant improvements in pain interference and pain intensity, and in emotional measures such anxiety and depression. Functional connectivity in the NET group compared to controls, was significantly decreased in the amygdala, cerebellum, and postcentral gyrus. There were also significant correlations between FC changes and changes in clinical measures.Conclusions This study is an initial step towards describing a neurological signature of reducing emotional distress in women with chronic pelvic pain. Specifically, FC changes between the cerebellum and the amygdala and sensory areas appears to be associated with a reduction in pain and the effects of that pain. Future, larger clinical trials are warranted to further evaluate these mechanisms and NET as a potential therapeutic intervention in patients with chronic pelvic pain.